2021
DOI: 10.1080/1547691x.2021.1877375
|View full text |Cite
|
Sign up to set email alerts
|

In vitro prediction of in vivo pseudo-allergenic response via MRGPRX2

Abstract: In development of peptide therapeutics, rodents are commonly-used preclinical models when screening compounds for efficacy endpoints in the early stages of discovery projects. During the screening process, some peptides administered subcutaneously to rodents caused injection site reactions manifesting as localized swelling. Screening by postmortem evaluations of injection site swelling as a marker for local subcutaneous histamine release, were conducted in rats to select drug candidates without this adverse ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…From a patient perspective, defining the role of MRGPRX2 is important as if confirmed, it may provide predictive, preventative and therapeutic strategies for drug-induced anaphylaxis. Moreover, the pharmaceutical industry is increasingly examining drug agonism at MRGPRX2 in their pre-clinical drug candidate evaluations (11,12). In one such study, around 20% of a drug-screening chemical library was shown to be MRGPRX2-activating (11).…”
mentioning
confidence: 99%
“…From a patient perspective, defining the role of MRGPRX2 is important as if confirmed, it may provide predictive, preventative and therapeutic strategies for drug-induced anaphylaxis. Moreover, the pharmaceutical industry is increasingly examining drug agonism at MRGPRX2 in their pre-clinical drug candidate evaluations (11,12). In one such study, around 20% of a drug-screening chemical library was shown to be MRGPRX2-activating (11).…”
mentioning
confidence: 99%